Composite phase change material with three-layer core-shell structure and preparation method of composite phase change material
By adopting a composite phase change material with a three-layer core-shell structure, the combination of porous fly ash hollow microbeads, silica aerogel and n-octadecane phase change material is solved by solving the leakage and difficulty of double-layer core-shell structure materials. The problem of uniform dispersion achieves more efficient insulation performance and better mechanical properties.
Patent Information
- Application Number
- CN202411719597.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The silica aerogel composite phase change material with a double-layer core-shell structure is prone to leakage and difficult to disperse evenly in the concrete matrix, affecting its thermal insulation and mechanical properties.
A composite phase change material with three-layer core-shell structure, the outer shell is porous fly ash hollow microbead, the middle shell is a silica aerogel, and the core layer is a n-octadecane phase change material, which is treated by electrolysis. The nanopore size is formed, the heat transfer area is increased and the density is increased, thereby improving the thermal conductivity and heat storage and heat release rate.
It effectively reduces the loss of phase change materials, improves the insulation effect and density of composite materials, so that they can be evenly dispersed in concrete, reduces thermal conductivity and improves mechanical properties.
Smart Images

Figure CN119505826A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation and energy storage materials, and in particular relates to a composite phase change material with a three-layer core-shell structure and a preparation method thereof. Background Art
[0002] Silica aerogel is a new type of material with a three-dimensional network structure. It has the characteristics of high porosity, large specific surface area and low thermal conductivity. It is the most studied and mature high-temperature resistant aerogel in the field of thermal insulation and has gradually become a mainstream thermal insulation material. Researchers have found that organic or inorganic phase change materials can be filled into aerogels to enhance their degree of heat absorption and release without changing their thermal insulation properties.
[0003] Liquid paraffin as a phase change material can absorb or release a large amount of heat when the temperature changes, improve energy efficiency, and has significant applications in building energy conservation. Adding phase change materials to concrete can significantly improve the thermal insulation performance of concrete, extend service life and reduce energy consumption. The invention patent "A composite phase change gel thermal insulation energy storage material and its preparation method" with publication number CN115124976B fills paraffin phase change material into aerogel nanopores to obtain phase change aerogel. This double-layer core-shell structure of the phase change aerogel often cannot avoid the loss of phase change material. The phase change material will leak during the continuous phase change process, resulting in a decrease in the thermal insulation and heat storage capacity of the composite material. Moreover, this composite material has a low bulk density and a large difference in density with the concrete matrix. It is not easy to be evenly dispersed in the concrete, which will not only affect the overall mechanical properties and durability of the concrete, but also reduce the heat transfer efficiency of the phase change material in the concrete. Summary of the invention
[0004] In order to solve the problem that a double-layer core-shell structured silica aerogel composite phase change material is easy to leak and difficult to disperse evenly in a concrete matrix, the present invention provides a three-layer core-shell structured composite phase change material and a preparation method thereof.
[0005] The technical solution of the present invention:
[0006] A method for preparing a composite phase change material with a three-layer core-shell structure comprises the following steps:
[0007] Step 1: Preparation of porous fly ash hollow microspheres:
[0008] Using cryolite as electrolyte, dissolving it in water and stirring it evenly to obtain electrolyte, using graphite rods as two electrodes, adding fly ash hollow microbeads, electrolyzing at an electrolysis temperature of 970-1050°C and an electrolysis voltage of 0.7-1.40V, obtaining porous fly ash hollow microbeads with pores of 50-150nm on the surface, and washing the obtained porous fly ash hollow microbeads to neutrality and fully drying;
[0009] Step 2: Preparation of phase-change silica hydrosol:
[0010] The water glass and deionized water are mixed in a volume ratio of 1:3-6, and mechanically stirred to obtain a water glass solution, and the obtained water glass solution is passed through a strong acidic cation exchange resin at a certain flow rate to obtain a silica hydrosol with a pH of 3-5; the obtained silica hydrosol is mixed with n-octadecane at room temperature, and stirred evenly to obtain a phase change silica hydrosol;
[0011] Step 3: Preparation of phase-change silica hydrogel-porous fly ash hollow microspheres:
[0012] Under vacuum environment, the phase-change silica hydrosol obtained in step 2 is mixed with the porous fly ash hollow microspheres obtained in step 1, and after vacuum treatment for a certain period of time, the solid material floating on the upper layer of the obtained vacuum mixed system is collected and placed in a water bath at a certain temperature to obtain phase-change silica hydrogel-porous fly ash hollow microspheres;
[0013] Step 4: Preparation of a composite phase change material with a three-layer core-shell structure:
[0014] The phase-change silica hydrogel-porous fly ash hollow microspheres obtained in step 3 are immersed in anhydrous ethanol, treated in a water bath at a certain temperature, and the solid material is collected by filtration to obtain the phase-change silica hydrogel-porous fly ash hollow microspheres;
[0015] The obtained phase-change silica alcohol gel-porous fly ash hollow microspheres are immersed in a trimethylchlorosilane / n-hexane mixed solution, treated in a water bath at a certain temperature, and the solid material is collected by filtration to obtain phase-change silica silylated gel-porous fly ash hollow microspheres;
[0016] The obtained phase change silica silylated gel-porous fly ash hollow microbeads are immersed in n-hexane solution, the solid material is collected by filtration, and after standing for a certain period of time, it is dried in a stepwise heating environment to obtain a three-layer core-shell structured phase change silica aerogel-porous fly ash hollow microbead composite phase change material.
[0017] Furthermore, step one also includes the process of screening the fly ash hollow microbeads before electrolysis: pouring the fly ash hollow microbeads into water, selecting the fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully drying them for later use.
[0018] Furthermore, in step 1, the particle size of the fly ash hollow microspheres is 50-200 μm; the mass concentration of cryolite in the electrolyte is 20-30%; the electrolysis time is 60-120 min, and the sufficient drying condition is drying at 80-110° C. for not less than 12 h.
[0019] Furthermore, in step 2, the modulus of the water glass is 3.3M; the mechanical stirring is 300-360 r / min for 30-40 min, and the flow rate of the water glass solution through the strongly acidic cation exchange resin is 200-300 mL / h.
[0020] Furthermore, in step 2, the mass ratio of the silica hydrosol to n-octadecane is 0.5-0.8:0.15-0.24.
[0021] Furthermore, in step three, the solid-liquid ratio of the phase change silica hydrosol to the porous fly ash hollow microspheres is 20-40g:200mL, the vacuum degree of the vacuum environment is -0.03-0.08MPa, the vacuum treatment time is 30min, the water bath treatment temperature is 40°C, and the water bath treatment time is 6h.
[0022] Furthermore, in step 4, the solid-liquid ratio of the phase change silica hydrogel-porous fly ash hollow microspheres to anhydrous ethanol is 40-60 g:400 mL, the solid-liquid ratio of the phase change silica alcohol gel-porous fly ash hollow microspheres to trimethylchlorosilane / n-hexane mixed solution is 40-60 g:200 mL, and the molar ratio of trimethylchlorosilane to n-hexane in the trimethylchlorosilane / n-hexane mixed solution is 1:2-1:3; the solid-liquid ratio of the phase change silica silylated gel-porous fly ash hollow microspheres to the n-hexane solution is 40-60 g:200 mL.
[0023] Furthermore, the water bath treatment in step 4 is carried out in a constant temperature water bath at 40°C for 24 hours, the standing is for 24 hours, and the stepwise drying treatment is carried out at 60°C, 80°C, 120°C and 160°C for 2 hours each.
[0024] The invention discloses a three-layer core-shell composite phase change material, wherein the outer shell layer is porous fly ash hollow microbeads, the middle shell layer is silicon dioxide aerogel, and the core layer is n-octadecane.
[0025] Furthermore, the phase change temperature of the composite phase change material is 27-30°C.
[0026] Beneficial effects of the present invention:
[0027] The present invention provides a composite phase change material with a three-layer core-shell structure, with porous fly ash hollow microbeads with pores of 50 to 150 nm etched on the surface as the outer shell layer, silica aerogel as the middle shell layer, and n-octadecane phase change material as the core. The present invention increases the heat transfer area of the phase change material by adsorbing n-octadecane into the silica aerogel in the middle shell layer, thereby increasing its density and thus improving the thermal conductivity of the phase change material and the heat storage and heat release rate of the composite phase change material. The critical stress volume fraction of the pore size on the porous fly ash hollow microbeads in the outer shell layer is greater than the critical stress volume fraction of n-octadecane, which can prevent the leakage of the phase change material, effectively reduce the loss of the phase change material, and enable the composite phase change material to maintain a stable thermal insulation effect.
[0028] Compared with porous fly ash hollow microspheres and silica aerogel, the present invention increases the bulk density of the three-layer core-shell structure composite phase change material, so that it can be evenly dispersed in the concrete substrate, thereby better exerting the thermal insulation effect by increasing the addition amount and reducing the thermal conductivity of the concrete.
[0029] The preparation process of the composite phase change material with a three-layer core-shell structure of the present invention is simple to operate, easy to control, and the raw materials used are low in cost and easy to obtain, which is conducive to the large-scale production of composite phase change materials. The composite phase change material with a three-layer core-shell structure prepared by the present invention is suitable for the field of building energy conservation and energy storage, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a microscopic photograph of the porous fly ash hollow microspheres prepared in Example 1;
[0031] Figure 2 This is a micrograph of the composite phase change material with a three-layer core-shell structure prepared in Example 1. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0033] Example 1
[0034] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0035] The required materials for this embodiment are prepared according to the following weight parts:
[0036] 1.8 parts of fly ash hollow microspheres with a particle size of 100 to 120 μm,
[0037] 0.18 parts of n-octadecane,
[0038] 0.7 parts of water glass with a modulus of 3.3M,
[0039] 3 parts of strong acid cation exchange resin,
[0040] 3 parts of anhydrous ethanol,
[0041] 3 parts of n-hexane,
[0042] 0.7 parts of trimethylsilyl chloride,
[0043] 0.7 parts of deionized water.
[0044] The properties of the materials used in this example are described as follows:
[0045] (1) Fly ash hollow microspheres, with a particle size of 100-120 μm, smooth surface, silvery white spheres, thin shells with tiny pinholes, wall thickness of 3-10 μm, and specific surface area of 0.35-0.40 m 2 / g, bulk density is 250~450kg / m 3 , apparent specific gravity is 0.6~0.75g / cm 3 , which is 1 / 3 of fly ash, with a specific resistivity of 108-1011Ω·m, a refractoriness of 1600-1700℃, a load softening point of 1200℃, and a thermal conductivity of 0.081-0115W / (m·k) at room temperature. The contents of SiO2, Al2O3, CaO, MgO, Na2O, K2O, Fe2O3, TiO2, and SO3 in fly ash hollow microspheres are 56.60%, 34.60%, 0.92%, 0.47%, 0.56%, 1.44%, 3.37%, 1.30%, and 0.40%, respectively. 80% of the physical phase is glass phase, and the crystalline phase contains mineral components such as mullite and quartz.
[0046] (2) The phase change material is n-octadecane, with a melting point of about 25.2-29.9°C, a latent heat of phase change of 243.5 KJ / kg, and a density of 785 kg / m 3 , is a very stable substance.
[0047] (3) The particle size of the strong acid cation exchange resin is 0.3-1.2 mm, and the exchange capacity is ≥1.8 Na. Its function is to remove the sodium ions in the water glass (Formula 1) to prevent the prepared aerogel from containing sodium chloride crystals that affect the thermal conductivity.
[0048] Na2SiO3+H ++H2O→Si(HO)4 (1)
[0049] (4) n-Hexane, molecular weight is 86.18 g / mol, density is 0.655 g / cm 3 (20℃), the surface tension is about 18.4mN / m. Its functions: ① As a solvent for the surface hydrophobizing agent, it combines with the silanizing agent TMCS (trimethylchlorosilane) to make the surface of silica aerogel hydrophobic and prevent the aerogel from hygroscopicity and aging; ② Replace the water in the pores of the aerogel. The low surface tension of n-hexane greatly reduces the capillary pressure, making the drying process more gentle.
[0050] (5) Trimethylchlorosilane (TMCS), molecular weight is 108.64 g / mol, density is 0.857 g / cm 3 (25°C). Its function: The gel contains a large number of hydrophilic silanol groups (Si-OH). TMCS reacts with the silanol groups to generate trimethylsilyl groups (-Si(CH3)3) and hydrogen chloride, which changes the gel surface from hydrophilic to hydrophobic (Formula 2), making the aerogel-porous hollow microspheres resistant to moisture.
[0051] (CH3)3SiCl+Si-OH→Si-O-Si(CH3)3+HC (2)
[0052] (6) Cryolite (NA3ALF6): White fine crystals with a melting point of 1009°C. Its functions are: 1) It can lower the melting point of oxides and reduce the loss during the process; 2) It can enhance the conductivity of the electrolyte and improve the electrolysis efficiency.
[0053] (7) Anhydrous ethanol: purity 99.5%. Its function: Anhydrous ethanol can promote the chemical reaction of silica hydrogel during the aging process, so that the siloxane bonds (Si-O-Si) are further cross-linked, and the network structure and mechanical stability of the gel are enhanced.
[0054] The preparation method of the composite phase change material with a three-layer core-shell structure in this embodiment includes the following steps:
[0055] A method for preparing a composite phase change material with a three-layer core-shell structure comprises the following steps:
[0056] Step 1: Preparation of porous fly ash hollow microspheres:
[0057] Pour fly ash hollow microbeads with a particle size of 100-120 μm into water, select fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully dry them at 105° C.
[0058] Cryolite is used as an electrolyte, dissolved in water and stirred evenly to obtain an electrolyte with a mass concentration of cryolite of 25%, graphite rods are used as two electrodes, and the screened fly ash hollow microbeads are added. Electrolysis is carried out for 90 minutes under the conditions of an electrolysis temperature of 1010°C and an electrolysis voltage of 1.08-1.26V. During the electrolysis process, oxides such as silicon dioxide and aluminum oxide in the fly ash hollow microbeads are reduced to form a single substance to form pores on the surface, thereby obtaining porous fly ash hollow microbeads with pore sizes of 100-120nm on the surface. The obtained porous fly ash hollow microbeads are washed to neutrality, dried at 105°C for more than 12 hours for use.
[0059] Figure 1 The porous fly ash hollow microbeads prepared in this embodiment, as can be seen from the figure, have nano-scale pores etched on the surface of the fly ash hollow microbeads.
[0060] Step 2: Preparation of phase-change silica hydrosol:
[0061] Water glass with a modulus of 3.3M is mixed with deionized water in a volume ratio of 1:4 to obtain a water glass solution. Droplets of the obtained water glass solution are added into a strongly acidic cation exchange resin at a droplet addition rate of 250 mL / h to obtain a silica hydrosol with a pH of 3. Compared with an alkaline environment, an aerogel with a larger specific surface area and a smaller pore size can be prepared in an acidic environment.
[0062] The obtained silica hydrosol and n-octadecane were mixed at a mass ratio of 0.7:0.18 at room temperature, and stirred evenly to obtain a phase-change silica hydrosol.
[0063] Step 3: Preparation of phase-change silica hydrogel-porous fly ash hollow microspheres:
[0064] The phase change silica hydrosol obtained in step 2 and the porous fly ash hollow microspheres prepared in step 1 are poured into a vacuum cylinder at a solid-liquid ratio of 20g:200mL. After ensuring that the phase change silica hydrosol submerges the porous fly ash hollow microspheres, the vacuum cylinder is sealed, the vacuum pump is turned on, and vacuum treatment is performed for 30 minutes at a vacuum degree of -0.08MPa. The solid material floating on the upper layer of the obtained vacuum mixed system is collected and placed in a constant temperature water bath at 40°C for 6 hours to obtain phase change silica hydrogel-porous fly ash hollow microspheres.
[0065] Step 4: Preparation of a composite phase change material with a three-layer core-shell structure:
[0066] The phase-change silica hydrogel-porous fly ash hollow microspheres obtained in step 3 are immersed in anhydrous ethanol at a solid-liquid ratio of 40 g:400 mL, and placed in a constant temperature water bath at 40° C. for 24 h, and the solid material is collected by filtration to obtain phase-change silica hydrogel-porous fly ash hollow microspheres;
[0067] The obtained phase change silica alcohol gel-porous fly ash hollow microspheres are immersed in a trimethylchlorosilane / n-hexane mixed solution at a solid-liquid ratio of 40 g:200 mL, wherein the molar ratio of trimethylchlorosilane to n-hexane in the trimethylchlorosilane / n-hexane mixed solution is 1:2, and the mixture is kept in a constant temperature water bath at 40° C. for 24 h, and the solid material is collected by filtration to obtain phase change silica silylated gel-porous fly ash hollow microspheres;
[0068] The obtained phase change silica silylated gel-porous fly ash hollow microspheres were immersed in n-hexane solution at a solid-liquid ratio of 40g:400mL, the solid material was collected by filtration, allowed to stand for 24h, and dried at 60°C, 80°C, 120°C and 160°C for 2h each to obtain a three-layer core-shell structured phase change silica aerogel-porous fly ash hollow microsphere composite phase change material.
[0069] Figure 2 This is a micrograph of the three-layer core-shell composite phase change material prepared in this embodiment. It can be seen from the figure that the outer shell layer of the composite material is porous fly ash hollow microbeads, the middle shell layer is silica aerogel, and the core layer is n-octadecane.
[0070] The specific effect and phase change principle of adsorbing n-octadecane to silica aerogel in this embodiment are as follows:
[0071] ① During the heat release process: When the temperature is below 27°C, the liquid solidifies into a solid and releases heat. Aerogel, as a three-dimensional continuous porous solid material, has low density, high porosity, high specific surface area and low thermal conductivity. Aerogel increases the heat transfer area and improves the interfacial thermal conductivity by adsorbing between the pore walls of the aerogel, thereby accelerating the heat storage and heat release rate of the phase change material.
[0072] ② During the endothermic process: above 27°C, it melts from solid to liquid to absorb heat, and the phase change material is adsorbed into the mesopores. Through the composite method of n-octadecane and silica aerogel, the super thermal insulation performance of silica aerogel material is brought into play, and the bubbles are divided into countless nano-scale pores. Since the nano-scale pore size is smaller than the mean free path of the gas therein, the gas in the pores adheres to the inner wall of the nano-pores and loses fluidity, thereby reducing the heat transfer caused by gas convection.
[0073] The following is the overall thermal conductivity formula of the three-layer core-shell structured phase change silica aerogel-porous fly ash hollow microsphere composite phase change material:
[0074] Because the thermal conduction of porous materials consists of four parts: thermal convection, gas thermal conduction, solid thermal conduction and thermal radiation, the overall thermal conductivity of the phase change silica aerogel-porous fly ash hollow microsphere composite phase change material can be expressed as:
[0075] λtot=λconv+λgas+λsolid+λrad (3)
[0076] Where λconv is the thermal conductivity contributed by thermal convection, which is caused by the gas temperature gradient in the pore structure. Since the diameter of the selected porous fly ash hollow microspheres is less than 1 mm, the contribution of thermal convection to the thermal conductivity can be ignored.
[0077] In the formula, the thermal conductivity contributed by the heat conduction of λgas gas is generated by the molecular collision in the structure. This part of the thermal conductivity is calculated by the following formula:
[0078] λgas=λga / 1+2βKn (4)
[0079] Kn=Lmean / Φ (5)
[0080] λga is the thermal conductivity of free gas, β is the coefficient of energy exchange between gas molecules and pore walls, which is generally 1.5 to 2.0, Kn is the Knudsen number, Lmean is the mean free path of gas molecules, and Φ is the pore size of the porous material.
[0081] From equations (4) and (5), it can be seen that gas heat conduction mainly depends on the pore size in the porous structure and the mean free path of gas molecules. When the phase change material occupies the volume of silica aerogel, it further limits the collision of gas molecules, thereby reducing thermal conductivity.
[0082] λsolid is the thermal conductivity contributed by solid heat conduction, which is caused by the lattice vibration in the porous structure skeleton. The calculation formula of this part of thermal conductivity is as follows:
[0083] λsolid=1 / 3pCvVaΛph (6)
[0084] In the formula, p is the solid density, Cv is the crystal specific heat capacity under the Debye model, Va is the average phonon velocity, and Λph is the phonon mean free path. The primary particle diameter of silica aerogel is about 2-5nm, and the phonon mean free path is about 0.58nm, which are at the same order of magnitude. Therefore, the solid heat transfer on the silica skeleton will be significantly reduced due to the microscale effect. In addition, the silica aerogel skeleton is a three-dimensional porous structure. After the adsorption of phase change materials, the solid heat transfer path is further complicated, thereby significantly reducing solid heat conduction.
[0085] λrad is the thermal conductivity contributed by radiation heat conduction. The calculation formula of this part of thermal conductivity is as follows:
[0086] λrad=16n 2 σB / 3ρK em T 3 (7)
[0087] Where n is the refractive index, is the Stefan-Boltzmann constant, and its value is 5.67x10-8W / (m 2 K4), ρ is the material density, K em is the average extinction coefficient, and T is the temperature. From the formula, we can see that radiative heat conduction is related to temperature, material density and extinction coefficient. As the temperature increases, the thermal conductivity also increases. In addition, the high-porosity silica aerogel adsorbs the phase change material, which has a strong scattering effect on thermal radiation, thereby effectively reducing radiative heat transfer.
[0088] Therefore, silica aerogel can effectively weaken the three heat transfer factors of gas heat conduction, solid heat conduction and radiation heat conduction by adsorbing n-octadecane.
[0089] The porous fly ash hollow microspheres as the shell have the following effects:
[0090] ① It has a hard shell that can protect the porous structure of silica aerogel from being destroyed;
[0091] ②Using porous fly ash hollow microspheres as the shell can prevent the leakage of phase change materials.
[0092] The porous fly ash hollow microspheres are selected as the shell: because n-octadecane is dispersed inside the porous fly ash hollow microspheres during the heat absorption process, there are many tiny pores inside the microspheres, and these tiny pores form a smaller interconnected random network. When these networks are not appropriate, n-octadecane is difficult to pass through. For this carbon particle, there is a critical value from a state that cannot pass to a state that can pass. When the plane stress volume ball formed by the particles gradually increases to the percolation threshold, more and more particles are associated with each other, and the superposition of the particle shear stress exceeds its shear yield stress, and then a percolation channel appears.
[0093] at this time:
[0094] S=Sc=dc+tc (8)
[0095] ∮s=∮sc= (Sc / dc)3∮rc (9)
[0096] From the above, we can get:
[0097] ∮sc= (dc+tc / dc)3∮rc (10)
[0098] Where S is the stress volume sphere diameter, Sc is the critical plane stress volume sphere diameter, dc is the critical phase change material particle size of about 2.81nm, ∮sc is the critical plane stress volume sphere fraction, ∮rc is the critical material volume fraction of about 0.214, and tc is the spacing between particles of about 10.09nm.
[0099] It can be concluded that d / S of n-octadecane is less than 0.8, the stress volume fraction sphere in the critical state remains basically unchanged, the stress volume fraction in the critical state is 0.206, the percolation threshold remains unchanged, each particle maintains an independent form and cannot be associated. When the selected pore size is between 50 and 150 nm, it can be seen from the above formula that its critical stress volume fraction is 0.213 to 0.345, so the critical stress volume fraction of the porous fly ash hollow microspheres is greater than the critical stress volume fraction of n-octadecane, that is, the shear yield stress of the porous fly ash hollow microspheres is greater than the shear stress between n-octadecane particles, and the selected porous fly ash hollow microsphere particle size can effectively prevent the leakage of n-octadecane.
[0100] Example 2
[0101] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0102] The only difference between this embodiment and embodiment 1 is that the particle size of the fly ash hollow microbeads used in this embodiment is 120-160 μm.
[0103] Example 3
[0104] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0105] The only difference between this embodiment and embodiment 1 is that the particle size of the fly ash hollow microbeads used in this embodiment is 160-200 μm.
[0106] Example 4
[0107] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0108] The difference between this embodiment and embodiment 1 is that, in step 1 of this embodiment, porous fly ash hollow microspheres are prepared:
[0109] Pour fly ash hollow microbeads with a particle size of 100-120 μm into water, select fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully dry them at 105° C.
[0110] Cryolite is used as an electrolyte, dissolved in water and stirred evenly to obtain an electrolyte with a mass concentration of cryolite of 25%, graphite rods are used as two electrodes, and the screened fly ash hollow microbeads are added. Electrolysis is carried out for 90 minutes under the conditions of an electrolysis temperature of 1010°C and an electrolysis voltage of 0.7-0.85V. During the electrolysis process, oxides such as silicon dioxide and aluminum oxide in the fly ash hollow microbeads are reduced to form a single substance, thereby forming pores on the surface, and porous fly ash hollow microbeads with pore sizes of 50-80nm on the surface are obtained. The obtained porous fly ash hollow microbeads are washed to neutrality, dried at 105°C for more than 12 hours for use.
[0111] Example 5
[0112] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0113] The difference between this embodiment and embodiment 1 is that, in step 1 of this embodiment, porous fly ash hollow microspheres are prepared:
[0114] Pour fly ash hollow microbeads with a particle size of 100-120 μm into water, select fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully dry them at 105° C.
[0115] Cryolite is used as an electrolyte, dissolved in water and stirred evenly to obtain an electrolyte with a mass concentration of cryolite of 25%, graphite rods are used as two electrodes, and the screened fly ash hollow microbeads are added. Electrolysis is carried out for 90 minutes under the conditions of an electrolysis temperature of 1010°C and an electrolysis voltage of 0.85-1.08V. During the electrolysis process, oxides such as silicon dioxide and aluminum oxide in the fly ash hollow microbeads are reduced to form a single substance to form pores on the surface, and porous fly ash hollow microbeads with pore sizes of 80-100nm on the surface are obtained. The obtained porous fly ash hollow microbeads are washed to neutrality, dried at 105°C for more than 12 hours and set aside.
[0116] Example 6
[0117] This embodiment provides a three-layer core-shell structure composite phase change material and a preparation method thereof.
[0118] The difference between this embodiment and embodiment 1 is that, in step 1 of this embodiment, porous fly ash hollow microspheres are prepared:
[0119] Pour fly ash hollow microbeads with a particle size of 100-120 μm into water, select fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully dry them at 105° C.
[0120] Cryolite is used as an electrolyte, dissolved in water and stirred evenly to obtain an electrolyte with a mass concentration of cryolite of 25%, graphite rods are used as two electrodes, and the screened fly ash hollow microbeads are added. Electrolysis is carried out for 90 minutes under the conditions of an electrolysis temperature of 1010°C and an electrolysis voltage of 1.26-1.40V. During the electrolysis process, oxides such as silicon dioxide and aluminum oxide in the fly ash hollow microbeads are reduced to form a single substance to form pores on the surface, thereby obtaining porous fly ash hollow microbeads with pore sizes of 120-150nm on the surface. The obtained porous fly ash hollow microbeads are washed to neutrality, dried at 105°C for more than 12 hours and set aside.
[0121] Comparative Example 1
[0122] This comparative example provides a composite phase change material with a three-layer core-shell structure and a preparation method thereof.
[0123] The difference between this comparative example and Example 1 is that, in step 1 of this comparative example, porous fly ash hollow microspheres are prepared:
[0124] Pour fly ash hollow microbeads with a particle size of 50 to 100 μm into water, select fly ash hollow microbeads with a complete hollow structure floating on the water surface, and fully dry them at 105° C.
[0125] Cryolite is used as an electrolyte, dissolved in water and stirred evenly to obtain an electrolyte with a mass concentration of cryolite of 25%, graphite rods are used as two electrodes, and the screened fly ash hollow microbeads are added. Electrolysis is carried out for 90 minutes under the conditions of an electrolysis temperature of 1010°C and an electrolysis voltage of 1.08-1.26V. During the electrolysis process, oxides such as silicon dioxide and aluminum oxide in the fly ash hollow microbeads are reduced to form a single substance to form pores on the surface, thereby obtaining porous fly ash hollow microbeads with pore sizes of 100-120nm on the surface. The obtained porous fly ash hollow microbeads are washed to neutrality, dried at 105°C for more than 12 hours for use.
[0126] The performance of the three-layer core-shell composite phase change materials prepared in Examples 1 to 6 and Comparative Example 1 was tested using conventional testing methods in the art. The results are shown in Table 1.
[0127] Table 1
[0128]
[0129] From the data comparison in Table 1, it can be seen that the composite phase change material with a three-layer core-shell structure provided by the present invention has a lower thermal conductivity and can better achieve a stable thermal insulation effect. At the same time, the phase change loss of the composite phase change material with a three-layer core-shell structure after 150 phase change cycles is only 0.06-0.21%, which indicates that the critical stress volume fraction of the pore size on the porous fly ash hollow microbeads in the outer shell layer is greater than the critical stress volume fraction of n-octadecane, which can prevent the leakage of the phase change material and effectively reduce the loss of the phase change material.
Claims
1. A method for preparing a three-layer core-shell composite phase change material, characterized in that: The steps include: Step 1: Preparation of porous fly ash hollow microspheres: Using cryolite as electrolyte, dissolving it in water and stirring it evenly to obtain electrolyte, using graphite rods as two electrodes, adding fly ash hollow microbeads, electrolyzing at an electrolysis temperature of 970-1050°C and an electrolysis voltage of 0.7-1.40V, obtaining porous fly ash hollow microbeads with pores of 50-150nm on the surface, and washing the obtained porous fly ash hollow microbeads to neutrality and fully drying; Step 2: Preparation of phase-change silica hydrosol: The water glass and deionized water are mixed in a volume ratio of 1:3-6, and mechanically stirred to obtain a water glass solution, and the obtained water glass solution is passed through a strong acidic cation exchange resin at a certain flow rate to obtain a silica hydrosol with a pH of 3-5; the obtained silica hydrosol is mixed with n-octadecane at room temperature, and stirred evenly to obtain a phase change silica hydrosol; Step 3: Preparation of phase-change silica hydrogel-porous fly ash hollow microspheres: Under vacuum environment, the phase-change silica hydrosol obtained in step 2 is mixed with the porous fly ash hollow microspheres obtained in step 1, and after vacuum treatment for a certain period of time, the solid material floating on the upper layer of the obtained vacuum mixed system is collected and placed in a water bath at a certain temperature to obtain phase-change silica hydrogel-porous fly ash hollow microspheres; Step 4: Preparation of a composite phase change material with a three-layer core-shell structure: The phase-change silica hydrogel-porous fly ash hollow microspheres obtained in step 3 are immersed in anhydrous ethanol, treated in a water bath at a certain temperature, and the solid material is collected by filtration to obtain the phase-change silica hydrogel-porous fly ash hollow microspheres; The obtained phase-change silica alcohol gel-porous fly ash hollow microspheres are immersed in a trimethylchlorosilane / n-hexane mixed solution, treated in a water bath at a certain temperature, and the solid material is collected by filtration to obtain phase-change silica silylated gel-porous fly ash hollow microspheres; The obtained phase change silica silylated gel-porous fly ash hollow microbeads are immersed in n-hexane solution, the solid material is collected by filtration, and after standing for a certain period of time, it is dried in a stepwise heating environment to obtain a three-layer core-shell structured phase change silica aerogel-porous fly ash hollow microbead composite phase change material.
2. The method for preparing a three-layer core-shell composite phase change material according to claim 1, characterized in that: Step one also includes the process of screening fly ash hollow microbeads before electrolysis: pour the fly ash hollow microbeads into water, select the fly ash hollow microbeads with complete hollow structure floating on the water surface, and fully dry them for later use.
3. The method for preparing a three-layer core-shell composite phase change material according to claim 1 or 2, characterized in that: Step 1: The particle size of the fly ash hollow microspheres is 50-200 μm; the mass concentration of cryolite in the electrolyte is 20-30%; the electrolysis time is 60-120 min, and the sufficient drying condition is drying at 80-110° C. for not less than 12 h.
4. The method for preparing a three-layer core-shell composite phase change material according to claim 3, characterized in that: In step 2, the modulus of the water glass is 3.3M; the mechanical stirring is 300-360r / min for 30-40min, and the flow rate of the water glass solution through the strongly acidic cation exchange resin is 200-300mL / h.
5. The method for preparing a three-layer core-shell composite phase change material according to claim 4, characterized in that: In step 2, the mass ratio of the silica hydrosol to n-octadecane is 0.5-0.8:0.15-0.
24.
6. The method for preparing a three-layer core-shell composite phase change material according to claim 5, characterized in that: In step 3, the solid-liquid ratio of the phase change silica hydrosol to the porous fly ash hollow microspheres is 20-40g:200mL, the vacuum degree of the vacuum environment is -0.03-0.08MPa, the vacuum treatment time is 30min, the water bath treatment temperature is 40°C, and the water bath treatment time is 6h.
7. The method for preparing a three-layer core-shell composite phase change material according to claim 6, characterized in that: In step 4, the solid-liquid ratio of the phase change silica hydrogel-porous fly ash hollow microspheres to anhydrous ethanol is 40-60 g:400 mL, the solid-liquid ratio of the phase change silica alcohol gel-porous fly ash hollow microspheres to trimethylchlorosilane / n-hexane mixed solution is 40-60 g:200 mL, and the molar ratio of trimethylchlorosilane to n-hexane in the trimethylchlorosilane / n-hexane mixed solution is 1:2-1:3; the solid-liquid ratio of the phase change silica silylated gel-porous fly ash hollow microspheres to the n-hexane solution is 40-60 g:200 mL.
8. The method for preparing a three-layer core-shell composite phase change material according to claim 7, characterized in that: The water bath treatment in step 4 is carried out in a constant temperature water bath at 40°C for 24 hours, the standing is for 24 hours, and the stepwise drying treatment is carried out at 60°C, 80°C, 120°C and 160°C for 2 hours each.
9. A three-layer core-shell structure composite phase change material prepared by the method for preparing a three-layer core-shell structure composite phase change material according to any one of claims 1 to 8, characterized in that: The outer shell layer is porous fly ash hollow microspheres, the middle shell layer is silica aerogel, and the core layer is n-octadecane.
10. The three-layer core-shell composite phase change material according to claim 9, characterized in that: The phase change temperature of the composite phase change material is 27-30°C.
Citation Information
Patent Citations
A composite phase change gel thermal insulation and energy storage material and its preparation method
CN115124976B
Method for simultaneously preparing SiO2 aerogel and zeolite by utilizing fly ash
CN101538046A
Method for extracting metal from coal ash by fused salt electrolysis method
CN103526234A
Nano-microporous thermal insulation material and preparation method thereof
CN109721323A
Solid-waste-containing light-weight, heat-preservation and high-strength geopolymer and preparation method thereof
CN114671634A